Peran keterlibatan ayah terhadap perilaku externalizing pada remaja yang dimediasi oleh keberfungsian keluarga - Vatin, Nurva Dillatul; Andayani, Budi (Konsorsium Psikologi Ilmiah Nusantara, 2025)
Externalizing behavior refers to problematic actions among adolescents, such as delinquency and aggression, which negatively affect both individuals and society. This study examined whether family functioning mediates the relationship between father involvement and adolescents’ externalizing behavior. Using a quantitative approach with convenience sampling, 198 adolescents aged 13–18 completed the offline survey. Regression-based mediation analysis showed that family functioning did not mediate the relationship, but father involvement significantly influenced adolescents’ externalizing behavior. The findings of this study highlight that father involvement plays a significant role in shaping adolescents’ externalising behaviour. These results can serve as a valuable reference for families to strengthen fathers’ engagement in parenting, particularly during their children’s transition into adolescence. Communities and government agencies may use these insights to design and implement parenting programs that promote active and sustained father participation in childrearing and education.